Real-World Cost of Nasal Polyps Surgery and Risk of Major Complications in the United States: A Descriptive Retrospective Database Analysis - Ge W; Wang D; Chuang CC; Li Y; Rout R; Siddiqui S; Kamat S (Dove Medical Press, 2022)
Wenzhen Ge,1 Degang Wang,1 Chien-Chia Chuang,2 Yongtao Li,3 Raj Rout,4 Shahid Siddiqui,1 Siddhesh Kamat1 1Health Economics and Outcomes Research, Medical Affairs, Regeneron, Tarrytown, NY, USA; 2Global Health Economics and Value Assessment, Sanofi, Cambridge, MA, USA; 3Global Medical Affairs, Sanofi, Bridgewater, NJ, USA; 4Global Medical Affairs, Sanofi, Reading, UKCorrespondence: Siddhesh Kamat, Email siddhesh.kamat@regeneron.comBackground: Endoscopic nasal polyp (NP) surgery is a treatment option for patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Previous studies report NP surgery costs of $8000- 13,000 and risk of major complications of NP surgery of ~0.1- 1%. Limited contemporary data for costs and complications associated with NP surgery in US clinical practice are available.Methods: IQVIA PharMetrics Plus claims data were used to identify patients with NP surgery in 2019 with ≥ 3 years continuous baseline health-plan enrollment prior to index date (date of first eligible NP surgery) and ≥ 30 days continuous enrollment after index (follow-up). In this descriptive analysis, total costs of NP surgery were estimated as all medical costs on the index date (or during the entire hospital stay for patients who received surgery in the inpatient setting). Total medical costs (all-cause) were estimated for all medical services occurring from the index date to the index date +9 or +29 days (10-day and 30-day). Major complication was defined as cerebrospinal fluid (CSF) leak, orbital injury, or major hemorrhage within 30 days of index.Results: Of 6311 patients, median age was 46 years (interquartile range: 34- 56); 59.7% were male; 88.2% had no NP surgery in the prior 3 years; 63.7% had allergic rhinitis, and 37.1% had asthma. Mean (SD) total medical cost of surgery was $14,697 (11,679) and mean (SD) 10-day total medical cost was $15,401 (11,968). Major complications occurred in 102 (1.7%) patients. Total medical costs and 10-day costs were higher in patients with major complications than those without ($23,605 [19,264] vs $15,251 [11,741]).Conclusion: In this descriptive analysis, NP surgery costs and rates of major surgical complications were updated using recent real-world data in the US. Results indicated that NP surgery complication rates were numerically higher than previously reported.Keywords: chronic rhinosinusitis with nasal polyps, nasal polyp surgery, real-world, complications, costs